Chemical ozone loss in the Arctic and Antarctic stratosphere between 1992 and 2005 - Tilmes, S.; Müller, R.; Engel, A.; Rex, M.; Russell, J. M. (Geophysical Research Letters, 2006)
[1] The magnitude of chemical loss of polar ozone induced by anthropogenic halogens depends on the extent of chlorine activation, which is controlled by polar stratospheric clouds (PSCs) and thus by temperature. We propose a new quantity, the PSC formation potential (PFP) of the polar vortex, suitable for comparing the amount of ozone depletion in the Arctic and Antarctic regions. PFP represents the fraction of the vortex, over an ozone loss season, exposed to PSC temperatures. Chemical ozone loss in the Arctic correlates well with PFP, for winters between 1991 and 2005. For Antarctic and cold Arctic winters, PFP has been increasing over the past 30 years. In winter 2005, PFP and ozone loss in the Arctic reached record highs, approaching Antarctic levels. Nevertheless, column ozone in spring in the Arctic is much larger than the Antarctic, because of larger dynamical resupply of ozone to the Arctic.